Engaging community health workers to promote oral health for people living with type 2 diabetes mellitus in Nepal: a qualitative study - Yuriko Harada; Prapti Giri; Dilip Prajapati; Haruka Sakamoto; Tomohiko Sugishita; Lal Rawal (BMC Primary Care)
Abstract Background People living with type 2 diabetes mellitus (T2DM) are likely to develop oral health problems, and vice versa. The burden of oral health and T2DM is increasing, especially in low- and middle-income countries. Access to oral health care remains a challenge in many countries, including Nepal. This study examined the challenges and opportunities for engaging community health workers (CHWs) in promoting oral health care among people with T2DM in Nepal. Methods This study used a qualitative research design using key informant interviews (KIIs) and in-depth interviews (IDIs) responding to open ended questions. Data were collected from health facilities across two districts, Kavrepalanchowk and Kathmandu. The IDIs were conducted with CHWs, including health assistants (n = 7) and community medical assistants (n = 4) from rural and semi-urban areas, while the KIIs were conducted with policy makers and health managers at central level (n = 7). Data was analysed thematically. Results The participants highlighted the importance and need for providing integrated oral health services at the primary care level. However, they pointed the challenges including (i) lack of policies, guidelines and provision of oral health care, especially for people with T2DM, (ii) lack of capacity on oral health among the CHWs, and (iv) inadequate resources and supplies at primary health care settings. These gaps presented opportunities to develop targeted policies and CHW training by ensuring continuous supervision and appropriate incentivisation, facilitating the integration of oral health care at primary health care level in Nepal. Conclusions The findings of study highlight the potential for engaging CHWs to deliver oral health services for people with T2DM at the primary health care level in Nepal. Strengthening the health system and building capacity of CHWs, along with continued supervision, incentivisation and supply of adequate resources could facilitate the integration of oral health services into primary health care settings in Nepal.